IMPACT OF IMPLEMENTING A SURGICAL SAFETY CHECKLIST IN HOSPITAL: LITERATURE REVIEW - Arimbi, Ezha Gadis Rekly; Dhamanti, Inge (Fakultas Ilmu Kesehatan, Kedokteran dan Ilmu Alam (FIKKIA), Universitas Airlangga, 2023)
ABSTRACT Background: The Surgical Safety Checklist is part of WHO's efforts to reduce the number of deaths worldwide. Purpose: To analyze the impact of implementing the WHO Surgical Safety Checklist in hospitals. Methods: Article search was carried out through PubMed and ScienceDirect databases using keywords (